Existence of solution for a class of activator–inhibitor systems. (12th January 2023) - Figueiredo, Giovany; Montenegro, Marcelo
Abstract: We prove the existence of a solution for a class of activator–inhibitor system of type - Δ u +u = f(u) -v, -Δ v+ v=u in R^N . The function f is a general nonlinearity which can grow polynomially in dimension N≥ 3 or exponentiallly if N=2 . We are able to treat f when it has critical growth corresponding to the Sobolev space we work with. We transform the system into an equation with a nonlocal term. We find a critical point of the corresponding energy functional defined in the space of functions with norm endowed by a scalar product that takes into account such nonlocal term. For that matter, and due to the lack of compactness, we deal with weak convergent minimizing sequences and sequences of Lagrange multipliers of an action minima problem.